2017
DOI: 10.1515/rrlm-2017-0030
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive quantification of liver fibrosis regression following successful treatment of chronic hepatitis C with direct acting antivirals

Abstract: Introduction. The past years have revolutionized the treatment of hepatitis C virus (HCV) infection, with high

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In Romania, the most prevalent HCV genotype is genotype 1, 93.46% of patients having the genotype 1B (4). Among the eligibility criteria, the level of fibrosis is an important factor (5). Liver biopsy is still considered the gold standard for the staging of fibrosis and the evaluation of necroinflammatory activity, despite its limitations: invasive, it does not allow a dynamic evaluation of fibrosis and life-threatening complications (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…In Romania, the most prevalent HCV genotype is genotype 1, 93.46% of patients having the genotype 1B (4). Among the eligibility criteria, the level of fibrosis is an important factor (5). Liver biopsy is still considered the gold standard for the staging of fibrosis and the evaluation of necroinflammatory activity, despite its limitations: invasive, it does not allow a dynamic evaluation of fibrosis and life-threatening complications (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…A small number of HCV infected patients in Romania were exposed to DAAs, since such regimens were only used there in clinical trials (11), limited studies (12,13) and for the treatment of chronic patients with advanced fibrosis (F3 and F4 scores) (14). A recent autochthonous study showed 100% SVR among subtype 1b chronic Romanian patients undergoing DAAs treatment with ombitasvir/paritaprevir/ritonavir, dasabuvir with and without ribavirin for 12 weeks and that the quantitative regression of liver stiffness was inversely correlated with the duration of the HCV infection (15).…”
Section: Introductionmentioning
confidence: 99%